Differential angiogenesis of bone and muscle endothelium in aging and inflammatory processes - Chiara Arrigoni; Paola Ostano; Simone Bersini; Martina Crippa; Maria Vittoria Colombo; Mara Gilardi; Luigi Zagra; Maurizia Mello-Grand; Ilaria Gregnanin; Carmen Ghilardi; Maria Rosa Bani; Christian Candrian; et al. (Communications Biology, 2023)
Angiogenic analysis and transcriptomics on bone and skeletal muscle endothelial cells from osteoarthritis patients reveal different inflammatory conditions have a different impact on these cell populations.